Implementação e desenvolvimento de aeroportos industriais - Jaqueline Monteiro da Silva (2008)
Increased global competition encourages the search businesses of manufacturing for delivery speed, flexibility, customized products and reduction of stocks. At the same time that several countries of the world aim the promotion of its economic development and technology, and increasing exports. Already the airports strategically seek the expansion of its market. The industrial model of airports can bring competitive advantage to businesses of manufacturing, promoting agility logistics and reduction of stocks. Moreover, can provide incentives to exports andeconomic development to the country, and to the airports can provide strategic gains from the capture of income for services not directly related to the air industry, increasing the flow of cargo and capture of airlines. This study aims to identify key factors of success and the construction of a model for implementation and development of industrial airports, the airport structure, in which they are installed high-tech companies, who import materials for production, manufacture its productsand intended to exports, with exemption from taxes on import and export. To achieve this objective was the tool used for modeling business EKD (Enterprise Knowledge Development) call jointly with the case study of the first Brazilian industrial airport. It has identified four factors related to the success of implementation and development of industrial airports. What about the Brazilian case, discoveries of this research show that the vast surveillance and bureaucracy generated by Brazilian legislation, regulatory model of the airport industry, hindering the development andstructure of the system.